Between Peace and Gender Justice: Islamic Court Mediators’ Perspectives in Divorce Mediation in West Sumatra - Mhd Yazid (Institut Agama Islam Negeri (IAIN) Pontianak, 2026)
This article examines mediators’ perspectives on efforts to achieve gender justice in divorce cases within Islamic courts. This topic is significant given the strategic role of mediators in facilitating reconciliation while simultaneously protecting the rights of the parties involved. Utilizing a gender-based approach, this study explains how mediators understand and implement the concept of gender justice during the mediation process in six Islamic courts in West Sumatra. Based on field research conducted from July to October 2023, this study involved interviews with five judge mediators and three non-judge mediators. The research findings indicate that although mediators generally do not oppose the importance of justice, for them, justice is not the ultimate goal of mediation. Mediation is considered more focused on achieving peace. This assumption is subsequently followed by gender-biased stigmas that affect the gender sensitivity of the mediators. Nevertheless, some mediators have made efforts to realize gender justice, yet this depends more on individual and technical gender sensitivity and skills. These findings indicate that mediators are often caught between peace as the goal of mediation and justice as a moral standard, which results in limited protection for women during the mediation process. [Artikel ini mengkaji perspektif para mediator terhadap upaya mewujudkan keadilan gender dalam kasus perceraian di Pengadilan Agama. Topik ini menjadi penting mengingat peran strategis mediator dalam memfasilitasi perdamaian sekaligus melindungi hak-hak para pihak yang terlibat. Dengan menggunakan pendekatan berbasis gender, studi ini menjelaskan bagaimana para mediator memahami dan mengimplementasikan konsep keadilan gender dalam proses mediasi di enam pengadilan agama di Sumatera Barat. Berdasarkan penelitian lapangan yang dilakukan dari Juli sampai Oktober 2023, penelitian ini melibatkan wawancara dengan lima mediator hakim maupun tiga mediator non-hakim. Temuan penelitian menunjukkan bahwa meskipun secara umum para mediator tidak menolak pentingnya keadilan, bagi para mediator, keadilan bukan menjadi tujuan utama dalam mediasi. Mediasi dianggap lebih bertujuan untuk mewujudkan perdamaian. Asumsi ini, kemudian juga diikuti oleh adanya stigma bias gender yang mempengaruhi sensitivitas gender para mediator. Meskipun demikian, beberapa mediator sudah berupaya mewujudkan keadilan gender, namun lebih bergantung kepada keahlian dan sensitivitas gender individual. Temuan ini mengindikasikan bahwa para mediator kerap terjebak antara perdamaian sebagai tujuan mediasi dan keadilan sebagai standar moral, yang berdampak pada terbatasnya perlindungan terhadap perempuan dalam proses mediasi.]